2018
DOI: 10.3390/genes9090443
|View full text |Cite
|
Sign up to set email alerts
|

Global Long Noncoding RNA and mRNA Expression Changes between Prenatal and Neonatal Lung Tissue in Pigs

Abstract: Lung tissue plays an important role in the respiratory system of mammals after birth. Early lung development includes six key stages, of which the saccular stage spans the pre- and neonatal periods and prepares the distal lung for alveolarization and gas-exchange. However, little is known about the changes in gene expression between fetal and neonatal lungs. In this study, we performed transcriptomic analysis of messenger RNA (mRNA) and long noncoding RNA (lncRNA) expressed in the lung tissue of fetal and neon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 85 publications
4
10
0
Order By: Relevance
“…From the samples, 12,354 mRNA transcripts were expressed (FPKM >0.5 in at least one sample), and 5,946 lncRNA transcripts were substantially expressed (FPKM >0.1 in at least one sample). The lncRNAs shared similar features, such as relatively low exon numbers, low expression levels, short lengths, and low coding potentials, with previously reported vertebrate lncRNAs [14] (Supplementary Figure S2). Further analysis revealed that the number of expressed genes peaked at 180 days among the five time points.…”
Section: Messenger Rna and Lncrna Expression Profiles In Porcine Perisupporting
confidence: 78%
See 3 more Smart Citations
“…From the samples, 12,354 mRNA transcripts were expressed (FPKM >0.5 in at least one sample), and 5,946 lncRNA transcripts were substantially expressed (FPKM >0.1 in at least one sample). The lncRNAs shared similar features, such as relatively low exon numbers, low expression levels, short lengths, and low coding potentials, with previously reported vertebrate lncRNAs [14] (Supplementary Figure S2). Further analysis revealed that the number of expressed genes peaked at 180 days among the five time points.…”
Section: Messenger Rna and Lncrna Expression Profiles In Porcine Perisupporting
confidence: 78%
“…The transcripts that were annotated in the reference (marked by 'c' for partial matches and '=' for full matches) were removed using Coffcompare (part of Cufflinks, v.2.2.1). Next, transcripts longer than 200 nt were retained to predict coding potential using a previously described approach [14]. We considered a lncRNA transcript to be expressed if it had an expression value greater than 0.1 FPKM (FPKM >0.1) in at least one sample.…”
Section: Lncrna Identification and Expression Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…With the development of genetic array and high throughput sequencing technology, more and more lncRNAs have been discovered in human, rat and mouse (Zhao et al 2016). Recently, lncRNAs have also been identified in pig (Yang et al 2017;Jin et al 2018;Kern et al 2018), chicken (Muret et al 2017;Kern et al 2018;Li et al 2019), sheep (Ren et al 2016;Ling et al 2017;Bush et al 2018;Sulayman et al 2019) and cattle (Billerey et al 2014;Koufariotis et al 2015;Tong et al 2017;Bush et al 2018;Kern et al 2018;Weikard et al 2018;Yang et al 2018;Choi et al 2019;Wang et al 2019;Yue et al 2019).…”
Section: Introductionmentioning
confidence: 99%